Economic assessment of several agroforestry system and land use options in Malaysia: A review / Ahmad Fauzi Puasa, Najib Lotfy Arshad and Najidah Ibrahim - Puasa, Ahmad Fauzi; Arshad, Najib Lotfy; Ibrahim, Najidah (Universiti Teknologi MARA Cawangan Pahang, 2005)
The shortage of log supply became an alarming problem for Malaysia starting from 1995. Similar problem is encountered in the food sector, whereby the import bills has increased from RM4.6 billion to RM10 billion in 1997. It implies that extra effort needs to be done to increase food as well as log production. Agroforestry is one of the ways to solve this problem. Taking this issue into account, the main intention of this paper is to review the current agroforestry systems and land use option in tropical climate especially in Malaysia. This paper does not only review the current agroforestry system but also evaluate the economic feasibility of different types of agroforestry system available in Malaysia as well as for other tropical climate countries. This paper is expected to help the farmers to provide the economic criteria in selecting the right choice of agroforestry system for their farm.